Comments on "The phylogeny of post-Palaeozoic Asteroidea (Neoasteroidea, Echinodermata)" by A.S. Gale and perspectives on the systematics of the Asteroidea - Blake, Daniel B.; Mah, Christopher L. (Zootaxa, 2014)
A new, morphologically based classification of extant asteroids with comments on select fossils was published by A.S. Gale. Research approaches used limited sampling, and much literature treatment is not accurate and therefore misleading. We review these concerns, seeking to clarify argumentation on differing interpretations.